Intersectoral dynamics and economic growth in Ecuador - Fiess, Norbert M. (Policy research working paper, 2001)
The authors analyze sectoral growth in Ecuador using multivariate cointegration analysis. They find significant long-run relationships between the agricultural industrial and service sectors. Moreover, they are able to derive dynamic sector models that combine the short-run links between the three sectors with long-run dynamics. Their findings suggest that more attention should be paid to interdependencies in sectoral growth, since an improved understanding of intersectoral dynamics may facilitate the implementation of policy aimed at increasing economic growth in Ecuador--Summary